Conversion therapy with TACE, TKIs, and ICIs for unresectable BCLC stage B and C hepatocellular carcinoma - Wang, Zhuoran; Zhang, Cunzhen; Yin, Jianhua; Li, Nan (Frontiers in Immunology, 2025)
Background and aimsMost Hepatocellular carcinoma (HCC) diagnoses occur at advanced stages precluding radical surgical resections. Conversion therapy offers a viable chance for patients with unresectable HCC (uHCC) to become eligible for curative surgery. Despite the application of various treatment modalities for conversion therapy, uncertainties persist regarding its efficacy. Consequently, we collected clinical data to evaluate the prognosis of TACE+TKI+ICI conversion therapy and compared it with the prognoses of other conversion therapies in the literature. We aimed to elucidate the potential superiority of triplet therapy as the optimal option among the existing conversion therapy regimens, by using this comprehensive analysis.MethodsFrom January, 2019, to November, 2022, we collected data from 69 patients with HCC undergoing conversion therapy with the TACE+TKI+ICI triplet therapy. Ultimately, we analyzed data from 57 patients at BCLC Stages B and C in our study. We also conducted a comprehensive literature review on conversion therapy for uHCC by searching PubMed and Web of Science databases and gathered data from 9 studies comprising a total of 560 patients.ResultsThe conversion and disease control rate (DCR) in our cohort reached 14.0% (95% CI, 9.4–18.6%) and 66.7% (95% CI, 60.5–72.9%), respectively. When compared to the conversion rates in the literature, the triplet therapy demonstrated significant benefits, underscoring the potential efficacy of the TACE+TKI+ICIs triplet therapy.ConclusionOur results presented improved conversion rates in patients with uHCC following TACE+TKI+ICI triplet therapy. However, overall survival (OS) and recurrence-free survival (RFS) were similar to those of other treatment modalities in the literature.Clinical Trial RegistrationClinicalTrials.gov, identifier ChiCTR2400084896.